Effectiveness of PEARL Mobile Application in Enhancing the Academic Performance of Students in English - Ariane Pearl P. Medel; John Frederick B. Tesoro; Alberto D. Yazon; Cristopher F. Mendoza; Karen A. Manaig (Journal of Elementary and Secondary School, 2024)
This research aimed to test the effectiveness of the Packeted Electronically Assisted Reading Leaflets (PEARL) mobile application in enhancing students’ English academic performances. The researcher gained knowledge of declining reading comprehension skills, including Grade 7 reading levels, using the Philippine Informal Reading Inventory (PHIL-IRI), the official reading material from the Department of Education. However, due to the COVID-19 pandemic, the administration of this reading inventory has been put on hold due to its inapplicability. This study was conducted with Grade 7 Calamba Bayside Integrated School students from the Division of Calamba as respondents. A quasi-experimental technique, and administration of pretest, formative, and posttest, were used in this study. As for the data collection, the respondents' pretest, formative test, and post-test scores in the experimental and controlled groups were recorded weekly. There are 22 active students participated in the study through random sampling. Next, data analysis was performed using the T-test and Pearson’s formulas, respectively. Based on these findings, the researcher concluded that there was a significant difference between the pretest and posttest mean scores of the two groups, which indicates that the PEARL application is practical in enhancing English academic performance. Although there was only a medium-sized effect regarding the significant differences in the scores of the experimental group, it is concluded that several factors, like poor internet connectivity and technical difficulties, should be considered. The researcher also suggested that crafting instructional materials such as PEARL could improve students’ English proficiency.